1975
DOI: 10.3758/bf03213438
|View full text |Cite
|
Sign up to set email alerts
|

Partial reward, the negative contrast effect, and incentive averaging

Abstract: A total of 169 rats distributed across six experiments, received training in a straight runwa Y d with a 5-min intertrial interval. A variety of shifts in reward schedules, to~nd from partial rewar , were employed to assess the effects of partial reward on the successi~e ne~atIve contrast effect. The results were seen as supportive of an incentive averaging approach to partial remforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The reinforcement-level theory (Capaldi, 1974) states that contrast is due to a discrepancy from an average, or expected, level of reinforcement. There are substantial data which show that animals average different levels of reward received in the past and that degree of contrast is a function of degree of discrepancy from this average level of reward (Flaherty, Becker, & Osborne, in press;McHose & Peters, 1975). The failure of negative contrast to diminish substantially with repeated shifts in any of these experiments indicates that the expected reward level is quickly "reset" to the maximum value when animals are returned to the preshift reward.…”
Section: Discussionmentioning
confidence: 95%
“…The reinforcement-level theory (Capaldi, 1974) states that contrast is due to a discrepancy from an average, or expected, level of reinforcement. There are substantial data which show that animals average different levels of reward received in the past and that degree of contrast is a function of degree of discrepancy from this average level of reward (Flaherty, Becker, & Osborne, in press;McHose & Peters, 1975). The failure of negative contrast to diminish substantially with repeated shifts in any of these experiments indicates that the expected reward level is quickly "reset" to the maximum value when animals are returned to the preshift reward.…”
Section: Discussionmentioning
confidence: 95%
“…Successive contrast effects pose a serious challenge to accounts of rational choice in which past states or alternative current states are irrelevant (6). So far, all theories to explain the existence of contrast effects have been based on descriptive models of psychological or physiological processes (4,7,(15)(16)(17)(18), largely ignoring their evolutionary basis [though see (10)]. Here we address this gap, by developing a simple and general optimality model to show that both positive and negative successive contrast effects can arise from an adaptive response to uncertainty about how conditions change over time.…”
mentioning
confidence: 99%
“…Previous studies (McHose & Peters, 1975;Mikulka et al, 1967) have clearly shown that partial reward in the preshift period attenuates the negative contrast effect. Since partial as compared to continuous reward should affect the intensity of K through the laws of classical conditioning, it follows that subjects trained on large partial reward and subsequently shifted to small continuous reward should display less contrast than subjects shifted from large to small continuous reward.…”
Section: Negative Contrastmentioning
confidence: 85%
“…For present purposes, this simply means that HA and HK differences between groups trained on partial as compared to continuous reward are no more nor less complicated than such differences for groups trained on different amounts of continuous reward (cf. McHose & Peters, 1975, for a detailed account of the various effects of partial and varied reward on negative contrast that are described by this approach). That the current model also provides a nice fit to the data bearing upon the effects of partial reward on positive contrast may be seen by reference to a study by Lehr (1974), in which positive contrast was obtained following a shift from small to large partial reward (as compared to a large partial-reward control condition).…”
Section: Negative Contrastmentioning
confidence: 99%
See 1 more Smart Citation